Incidence, determinants and impact of acute kidney injury in ACS patients with versus without diabetes mellitus. (14th October 2021) - Shiyovich, A; Skalsky, K; Steinmetz, T; Eisen, A; Samara, A; Beigel, R; Kornowski, R; Orvin, K
Abstract: Introduction: Acute kidney injury (AKI) is a common complication in patients presenting with acute coronary syndrome (ACS), particularly following percutaneous coronary intervention (PCI). Patients with diabetes mellitus (DM) are considered to be at increased risk for AKI in this setting. However, data regarding the incidence, risk factors and outcomes of AKI in diabetic patients compared to non-diabetics presenting with ACS is scarce. Purpose: To evaluate the incidence, risk factors and outcomes of AKI in patients with vs. without DM who are admitted with ACS. Methods: ACS patients enrolled in the biannual ACS Israeli Surveys (ACSIS) between 2000 and 2018 were analyzed. AKI was defined as an absolute increase in serum creatinine (≥0.5 mg/dL) or above 1.5 mg/dL or new renal replacement therapy upon admission with ACS. Outcomes included 30-day major adverse cardiovascular events (MACE) and 1-year all-cause mortality. Results: The current study included a total of 16, 879 patients, median age 64 (IQR 54–74), 77% males, 36% with DM. The incidence of AKI was significantly higher among patients with vs. without DM (8.4% vs. 4.7%, p<0.001). The rates of 30-day MACE (40.8% vs. 13.4%, p<0.001) and 1-year mortality (43.7% vs. 10%, p<0.001) were significantly greater among patients who developed vs. those that did not develop AKI respectively yet very similar in diabetics and non-diabetics. Multivariate analyses (figure 1) adjusted to potential confounders showed similar independent predictors of AKI among patients with and without DM comprising; older age, chronic kidney disease, congestive heart failure, and peripheral arterial disease Conclusions: Although patients with DM are at greater risk for AKI when admitted with ACS, the independent predictors of AKI and the worse patient outcomes when AKI occurs, are similar and irrespective to DM. FUNDunding Acknowledgement: Type of funding sources: None.